ChemInform Abstract: Advances in Nanomaterial Based Approaches for Enhanced Fluoride and Nitrate Removal from Contaminated Water. Issue 13 (March 2016) - Suriyaraj, S. P.; Selvakumar, R.
Abstract: Review: 195 refs.